2009
DOI: 10.1017/s0007114509992017
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D supplementation reduces insulin resistance in South Asian women living in New Zealand who are insulin resistant and vitamin D deficient – a randomised, placebo-controlled trial

Abstract: Low serum 25-hydroxyvitamin D (25(OH)D) has been shown to correlate with increased risk of type 2 diabetes. Small, observational studies suggest an action for vitamin D in improving insulin sensitivity and/or insulin secretion. The objective of the present study was to investigate the effect of improved vitamin D status on insulin resistance (IR), utilising randomised, controlled, double-blind intervention administering 100 mg (4000 IU) vitamin D 3 (n 42) or placebo (n 39) daily for 6 months to South Asian wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
439
3
11

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 564 publications
(481 citation statements)
references
References 46 publications
28
439
3
11
Order By: Relevance
“…This finding also argues against the possibility that reduced renin levels drove the fall in blood pressure observed in this study. Several studies have demonstrated that vitamin D can improve insulin resistance in patients with prediabetic states including insulin resistance and impaired glucose tolerance [10,11,25,26]. However, studies examining the effect of vitamin D on insulin resistance and glycaemic control in patients with established type 2 diabetes have been negative [9,10], and the large Women's Health Initiative study [27] found no reduction in new diagnoses of diabetes in participants receiving calcium plus a small (400 IU per day) dose of vitamin D 3 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding also argues against the possibility that reduced renin levels drove the fall in blood pressure observed in this study. Several studies have demonstrated that vitamin D can improve insulin resistance in patients with prediabetic states including insulin resistance and impaired glucose tolerance [10,11,25,26]. However, studies examining the effect of vitamin D on insulin resistance and glycaemic control in patients with established type 2 diabetes have been negative [9,10], and the large Women's Health Initiative study [27] found no reduction in new diagnoses of diabetes in participants receiving calcium plus a small (400 IU per day) dose of vitamin D 3 .…”
Section: Discussionmentioning
confidence: 99%
“…A number of small studies failed to show any improvement in glycaemic control or indices of insulin sensitivity during supplementation [2,9,10], although supplementation in patients with impaired glucose tolerance but without frank diabetes did successfully improve insulin resistance in two trials [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the best available inflammatory biomarker is CRP, an acute phase reactant that is a reliable, independent predictor of the risk of myocardial infarction, stroke and cardiovascular death (111) . Clinical trials of vitamin D supplementation show inconsistent results regarding an effect on CRP concentrations: most report no effect (77,80,97,(112)(113)(114)(115)(116) , whereas some show reductions in CRP concentrations (74,117,118) . Some trials have measured highsensitivity CRP (hsCRP), which can detect low-grade inflammation.…”
Section: Inflammationmentioning
confidence: 99%
“…Several large epidemiological studies have found 25(OH) D concentrations to be associated with improved insulin resistance and sensitivity (120)(121)(122) , but RCT have found mixed results; some have found a significant beneficial effect of supplementation (78,116,123) , while others have shown no effect (76,124) . An RCT in 100 apparently healthy, but centrally obese men observed an improvement in postprandial insulin sensitivity measured by the oral glucose insulin sensitivity index after supplementation with 3000 μg D 3 once a fortnight for 6 weeks: mean difference in change in oral glucose insulin sensitivity between placebo and the D 3 group was 41·1 (SE 15·5), P = 0·01 (78) .…”
Section: Insulin Sensitivity and Secretionmentioning
confidence: 99%
“…Oral magnesium supplementation, for example, improves insulin sensitivity, glucose homeostasis, and HbA1c levels in diabetic patients (Bo & Pisu, 2008). Several intervention studies have shown improved glycemic responses with vitamin D treatment, but these effects may be specific to individuals who were deficient at baseline or those who had preexisting metabolic disorders (von Hurst, Stonehouse, & Coad, 2010; Rice et al., 2011). The micronutrient profile of dairy could contribute to attenuated hyperglycemia as the cellular influx of calcium plays a pivotal role in nutrient intake and in endothelial‐dependent vasodilation, and magnesium is essential for optimal coupling and signaling through the insulin receptor (Rice et al., 2011; Zemel, 2001).…”
Section: Discussionmentioning
confidence: 99%